2013
DOI: 10.1186/2046-4053-2-18
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and network meta-analysis of interventions for fibromyalgia: a protocol

Abstract: BackgroundFibromyalgia is associated with substantial socioeconomic loss and, despite considerable research including numerous randomized controlled trials (RCTs) and systematic reviews, there exists uncertainty regarding what treatments are effective. No review has evaluated all interventional studies for fibromyalgia, which limits attempts to make inferences regarding the relative effectiveness of treatments.Methods/designWe will conduct a network meta-analysis of all RCTs evaluating therapies for fibromyalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 70 publications
0
11
0
2
Order By: Relevance
“…The available treatments that are directed toward FMS are highly variable, and long-term prospective observational studies have found that patient outcomes are typically poor [7][8][9]. A survey of 1200 primary care physicians in the USA (33 % response rate) found that only 14 % of respondents indicated very good or excellent satisfaction with the management of patients with FMS and other medically unexplained symptoms [10].…”
Section: Introductionmentioning
confidence: 99%
“…The available treatments that are directed toward FMS are highly variable, and long-term prospective observational studies have found that patient outcomes are typically poor [7][8][9]. A survey of 1200 primary care physicians in the USA (33 % response rate) found that only 14 % of respondents indicated very good or excellent satisfaction with the management of patients with FMS and other medically unexplained symptoms [10].…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgia is a complex painful syndrome, accompanied by a series of psychological and behavioral alterations (Busse et al, 2013), and characterized by chronic musculoskeletal pain (Wolfe et al, 2010). The hallmark symptom is chronic widespread pain, but patients also present fatigue, depression, cognitive dysfunctions, and sleep disturbances (Ceko et al, 2012;Wolfe et al, 2010).…”
Section: Analgesic Actions Of Resolvinsmentioning
confidence: 99%
“…9 Fibromyalgia prevalence in overall levels is between 2% and 5% of the world population, and it predominates in people about 20 and 50 years old, 10 with a higher proportion of women (10 times more than men). 11 The total amount of affected people in different countries are not negligible 12 : 3.2% in Germany, 2.4% in Spain, 2% in the United States, 1.4% in France, 3.7% in Italy, 3.6% in Portugal, and 2.5% in Sweden. In Spain, 15% of the rheumatology consults and between 5% and 10% of the primary health care are dedicated to these patients, which mean a total expense in public health of about 11 million euros per year.…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgia prevalence in overall levels is between 2% and 5% of the world population, and it predominates in people about 20 and 50 years old, with a higher proportion of women (10 times more than men) . The total amount of affected people in different countries are not negligible 12 : 3.2% in Germany, 2.4% in Spain, 2% in the United States, 1.4% in France, 3.7% in Italy, 3.6% in Portugal, and 2.5% in Sweden.…”
Section: Introductionmentioning
confidence: 99%